Implementasi Kebijakan Pendidikan Islam di Indonesia - Dewanti, Erisa Nada; Setiawan, Farid; Tobasa, Majelis Rena; Ediansyah, Pemi (Lembaga Yasin AlSys, 2022)
Implementation is the most important policy element, and the policy implementation process is a very important final determinant of policy making. Policy implementation is an activity that is seen after a valid direction has been issued from a policy which includes efforts to manage inputs to produce outputs or outcomes for the community. The implementation of education policy is one of the activities in the policy process that determines a policy in contact with equal educational stakeholders can be accepted by the community. Policy implementation is a complicated matter with a complex process. This journal article discusses the implementation of education policy implementation in Indonesia, and the research method used is qualitative by quoting from various sources. The purpose of the research is to obtain information about the implementation of educational policies, influencing factors, approaches, methodologies, and several probes of education in Indonesia. The results of this study are, 1. The implementation of educational policies is the implementation of the results of policies set by officials related to the implementation of education, 2. Factors that influence the implementation of educational policies, among others, resources, communication, disposition, and structure, 3. Approach in implementation education is top down, bottom up, procedural and managerial, and also political approaches.